PERGESERAN FUNGSI TARI ELANG NGINANG PADA MASYARAKAT DAYAK MUALANG DI BELITANG KABUPATEN SEKADAU - Inita, Andar; Ismunandar, Ismunandar; Satrianingsih, Aline Rizky Oktaviari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Mengayau, a traditional practice of the Dayak tribe involving headhunting, has historically served as a means of protection and territorial defense against perceived threats. Central to this tradition is the Elang Nginang dance, originally performed as part of ritualistic ceremonies, signifying communication with ancestral spirits and nature's forces. However, contemporary socio-political dynamics, particularly government regulations prohibiting sacred or magical rituals, have prompted a transformation in the function of the Elang Nginang dance among the Mualang Dayak community in Belitang, Sekadau District. Employing qualitative research methods rooted in anthropology, this study explores the evolution of the Elang Nginang dance's purpose within this cultural context. Through interviews and documentary analysis, findings reveal that government restrictions have compelled a shift in the dance's role, leading to its adaptation from a solitary ritual to a group performance. Furthermore, alterations in choreography, such as the involvement of five dancers arranged in a specific formation and the introduction of vertical floor patterns, underscore the impact of these changes on the dance's traditional form and function. This research sheds light on the intricate interplay between tradition, governance, and cultural expression within indigenous communities, highlighting the dynamic nature of cultural practices in response to external influences.